2019
DOI: 10.24106/kefdergi.3051
|View full text |Cite
|
Sign up to set email alerts
|

Fen, Teknoloji, Mühendislik ve Matematik (STEM) Eğitimi Etkinlik Örneği: Pıhtı Önleyici İlaç

Abstract: ÖzBu araştırmada, bir STEM etkinliğinin geliştirilmesi ve birinci sınıf fen bilgisi öğretmen adaylarına uygulanma sürecinin sunulması amaçlanmaktadır. Etkinlik geliştirme sürecine problem ve konunun belirlenmesi ile başlanmıştır. Etkinlik konusu belirlenirken Genel Kimya Laboratuvarı II ders içeriğinde yer alan ve hâlihazırda uygulanan deneyler kapsamında STEM eğitim yaklaşımı ile mühendislik tasarım sürecinin işletilebildiği, günlük yaşam ile ilişkinin kurulabildiği, güvenlik, etik ve sağlık konusunda önlemle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
(24 reference statements)
0
5
0
1
Order By: Relevance
“…The objectives of the STEM activity have been determined according to acquisitions of secondary school science, mathematics, and technology courses' curriculums in Turkey (MNE, 2018). While developing activities according to the EDP steps of the STEM education approach, the 9 th -grade physics textbooks and the studies on the STEM approach in the literature were examined (Aydın & Karslı-Baydere, 2019;Hacıoğlu & Dönmez-Usta, 2020;Wendell & Lee, 2010;Karslı-Baydere, Hacıoğlu, & Kocaman, 2019;Karahan, Bilici, & Ünal, 2015). By presenting real-life problem/design challenges to the students by the researchers, they were made to work like scientists and engineers (Hynes et al, 2011;Wendell & Lee, 2010).…”
Section: The Implementation Of the Stem Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…The objectives of the STEM activity have been determined according to acquisitions of secondary school science, mathematics, and technology courses' curriculums in Turkey (MNE, 2018). While developing activities according to the EDP steps of the STEM education approach, the 9 th -grade physics textbooks and the studies on the STEM approach in the literature were examined (Aydın & Karslı-Baydere, 2019;Hacıoğlu & Dönmez-Usta, 2020;Wendell & Lee, 2010;Karslı-Baydere, Hacıoğlu, & Kocaman, 2019;Karahan, Bilici, & Ünal, 2015). By presenting real-life problem/design challenges to the students by the researchers, they were made to work like scientists and engineers (Hynes et al, 2011;Wendell & Lee, 2010).…”
Section: The Implementation Of the Stem Activitymentioning
confidence: 99%
“…Step 5. Construct a prototype: A prototype is a model (physical, virtual or mathematical) that represents the final solution (Hynes et al, 2011;Karslı-Baydere et al, 2019;NRC, 2012). The most important feature of this state is that iterative prototyping until an acceptable product is reached, and the students physically create a solution model (Koehler, Latif, Faraclas, Sanchez, & Kazerounian, 2005).…”
Section: The Implementation Of the Stem Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Bu durum da STEM etkinliklerinin iş birliği içerisinde herkesi ilgilendiren bir problem üzerinde çözüm odaklı bir yaklaşımla çalışmalarına katkı sağladığı şeklinde yorumlanabilir. Nitekim STEM etkinliklerinin grup çalışmalarını desteklediği yönündeki sonuçlar bu durumu desteklemektedir (Aydın ve Karslı-Baydere, 2019;Karslı-Baydere ve Kurtoğlu, 2019). STEM etkinliklerinin öğretmen adayları açısından diğer avantajları arasında merak uyandırma yer almaktadır.…”
Section: Bulgularunclassified
“…These stages are (1) introducing the problem, (2) determining the needs, (3) developing solution suggestions, (4) choosing the best solution, (5) making the prototype, (6) testing and evaluating the solution, (7) presenting the solution, (8) redesign and (9) completion of the design. When the studies in the literature on STEM education are examined, it is seen that there are many activities developed and implemented according to EDP (Aydın and Karslı-Baydere, 2019;Eroğlu and Bektaş, 2016;Gökbayrak and Karışan, 2017;Karslı-Baydere and Kurtoğlu, 2019;Tarkın-Çelikkıran and Aydın-Günbatar, 2017;Yıldırım and Altun, 2015;Yıldırım, 2017). However, no study has been found to develop a design to prevent tooth decay in the teaching of the topic "bacteria and dental health", which is one of the problems of our daily life and which concerns us all.…”
Section: Teşekkürmentioning
confidence: 99%